Kierkegaard's Fear and trembling : a critical guide - Conway, Daniel W. (Editor) (Cambridge University, 2015)
"Written by an international team of contributors, this book offers a fresh set of interpretations of Fear and Trembling, which remains Kierkegaard's most influential and popular book. The essays provide incisive accounts of the psychological and epistemological presuppositions of Fear and Trembling; of religious experience and the existential dimension of faith; of Kierkegaard's understanding of the relationship between faith and knowledge; of the purported and real conflicts between ethics and religion; of Kierkegaard's interpretation of the value of hope, trust, love and other virtues; of Kierkegaard's debts to German idealism and Protestant theology; and of his seminal contributions to the fields of psychology, existential phenomenology and literary theory. The volume will be of great interest to scholars and upper-level students of Kierkegaard studies, the history of philosophy, theology and religious studies"--Provided by publisher.